Chinese airport again chooses inge GmbH's membranes after substantially benefiting from its technology for ten years. Issue 10 (October 2019) - Atkinson, Simon
Abstract : Ultrafiltration modules from membrane technology company inge GmbH have been running successfully for ten years at China's Beijing Airport. However, they are being replaced with the German company's next generation of modules because the operator is required to apply stricter standards to water treatment under a new directive issued by the Chinese government. This article provides the background to the original installation of membrane modules in 2008, their subsequent use and briefly describes the use of the firm's latest technology to upgrade the existing plant.